2020
DOI: 10.1177/0194599820915472
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Pain and Opiate Use after Endoscopic Sinus Surgery

Abstract: Objective To evaluate postoperative opiate use and patients’ opinions regarding pain management after endoscopic sinus surgery (ESS). Study Design Case series with planned data collection. Setting Tertiary referral medical center. Subjects and Methods We prospectively evaluated postoperative opiate utilization in adults undergoing ESS over a 2-year period at an academic medical facility. Exclusion criteria included use of nasal packing, intracranial or orbital procedures, tumor surgery, and any use of endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Specifically, NSAIDs have been avoided after FESS because of the risk of epistaxis. However, NSAIDs have been shown to be safe and effective in perioperative pain management after FESS and nasal surgeries in several recent studies . There is growing evidence that NSAIDs may decrease the requirement for rescue analgesics, including opioids .…”
mentioning
confidence: 99%
“…Specifically, NSAIDs have been avoided after FESS because of the risk of epistaxis. However, NSAIDs have been shown to be safe and effective in perioperative pain management after FESS and nasal surgeries in several recent studies . There is growing evidence that NSAIDs may decrease the requirement for rescue analgesics, including opioids .…”
mentioning
confidence: 99%
“…A recently published prospective case series of 64 patients by Ndon et al demonstrated that the average number of narcotic pills consumed over a 7‐day postoperative period was 7.7 (SD 7.6). This study identified no demographic or surgical risk factors but did find that narcotic use correlated with higher POD1 pain scores ( P < .001) 5 . Studies in the literature assessing pain levels after FESS and non‐narcotic pain management alternatives, however, remain sparse.…”
Section: Introductionmentioning
confidence: 74%
“…Sethi et al showed that typically 15.6 tablets were prescribed for patients following ESS, 3 and Ndon et al showed that mean opioid use over a 7-day period after ESS was 7.7 pills (SD ± 7.6). 7 EETS patients received a similar amount (15.7 tablets) on discharge, likely because EETS is an inpatient surgery, compared to ESS being an outpatient surgery; thus, opioid requirements by the day of discharge were lower than if they were discharged on the day of surgery. A limitation of our study, given its retrospective nature, is that we did not ask patients to prospectively record their analgesia usage at home, which would provide a more accurate measure of post-discharge analgesia usage.…”
Section: Discussionmentioning
confidence: 99%
“…3 Improving opioid prescribing practices, both in the hospital and on discharge, remains a key strategy in curtailing the quantity of prescriptions and, thereby, minimizing opportunities for prescription diversion and opioid-related complications. 4 Recent studies have looked at optimizing perioperative pain regimens among patients undergoing endoscopic sinus surgery (ESS) 3,[5][6][7][8] and septorhinoplasty. 9 Few studies have examined pain management after endoscopic endonasal transsphenoidal surgery (EETS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation